Harmonization of Health Law Number 17 of 2023 with the Legal Status of Hospitals as Legal Entities - Abdillah, Zaini; Ruslina, Elli; Azalia, Miliani; Pramulita, Ni Kadek Ayu; Wiguna, Andri (Inovasi Pratama Internasional. Ltd, 2025)
Based on Law Number 17 of 2023 concerning Health, it is stated that a hospital is a health service facility that provides comprehensive individual health services through promotive, preventive, curative, rehabilitative, and/or palliative health services by providing inpatient, outpatient, and emergency services. Referring to the provisions contained in Law Number 17 of 2023 concerning Health, hospitals can be organized by the central government, regional governments, or the community. Hospitals organized by the central government or regional governments in providing health services can apply the financial management pattern of public service agencies in accordance with the provisions of laws and regulations. In contrast, hospitals established by the community must be in the form of a legal entity whose business activities are only engaged in health services, except for hospitals organized by non-profit legal entities.